Chromatid associations in acrocentric chromosomes: evidence against nonrandomness. - Donahue, R P (1982)
Acrocentric chromosome associations from peripheral blood cultures of four normal individuals were examined after two replication cycles in bromodeoxyuridine (BrdU) using the FPG technique. Altogether, 167 out of 328 associations, or 51%, were concordant, having opposed chromatids similarly stained, and 49% discordant, thus indicating a random association of chromatids. None of the individual cultures revealed any significant departure from random chromatid association. Variation among individuals ranged from 38% to 58% concordance but repeat cultures did not indicate any consistent direction to the departure from 50%. Furthermore, neither the concentration of BrdU nor the type of association scored had any significant effect on the randomness of chromatid association. Thus, in contrast to another recent report, we found no evidence for a nonrandom alignment of chromatids in associated acrocentric chromosomes.